The Dynamics of Finance-Growth-Inequality Nexus: Theory and Evidence for India - Pranab Kumar Das; Bhaswati Ganguli; Sugata Marjit; Sugata Sen Roy (Center for Economic Studies and ifo Institute (CESifo), 2018)
The purpose of this research study has been to expand our understanding of the finance-growth `nexus' to finance-growth-inequality `nexus' in the presence of both the formal and the informal sources of borrowing. Using empirical evidence of IHDS Survey data for two rounds the study attempts to assess the co-evolution of finance-growth-inequality in an intertemporal framework. The most important finding of the paper pertains to the econometric result that the household asset grows at the same rate independent of the source of loans - banks or moneylenders though the level effect (intercept) is higher if the loan is obtained from banks or lower if the household lives below poverty line. The same also holds for the rate of growth of per capita income. There is virtually no significant difference for the households living below poverty line (BPL) on the rate of growth of capital asset or income whether source of borrowing is bank or money lender. This is then formalized in a theoretical model of intertemporal choice of entrepreneur-investor to show that if there are both formal and informal sources of borrowing with a constraint on the formal sector borrowing and no constraint on the latter, then growth rates of asset and income are determined by the informal sector interest rate. The result can be generalised for any number of sources of borrowing. This questions the conventional wisdom regarding the policy aimed at financial inclusion. Inequality of income increases independent of the source of borrowing, though the BPL households are worse off in general.
Keywords: C35; E50; G21; O11; 330; financial development; financial inclusion growth; inequality; bank; India; IHDS; logit model